Ocupação de terrenos de marinha: risco e regulamentação jurídica. - SANTOS, Jéssica de Souza Teixeira (Universidade Federal do Pará, 2019)
The present research has as objective to treat the marine lands and their increased, that as assets of the union, were also instituted as source of income of the same. Currently, they are enshrined in the federal constitution of 1988, as well as by decree-law no. 9,760 / 1946, by decree no. 3,725 / 2001, as well as by law no. 9,636 / 1988. The navy lands and their awnings may be established as sunday goods, goods of common use of the people and goods of special use. It is extremely important to also consider pec no. 39/2011, which aims at securing the land of the navy, as well as the question of the demarcation of these lands that is presented from the preamar average line of 1831, and the secretariat of the patrimony of the union - spu civil liability and the principles of environmental law, as well as the multidisciplinarity of disciplines of civil law, environmental law and disaster law, are necessary in order to the compression of the dimension of the subject and the problem presented. It is also understood that it is necessary to maintain the institute of marine lands as a good of the union, looking not only for the collection interest, but mainly for preservation, as well as for environmental recovery, transforming this institute into real service of the socio-environmental function and, moreover, as being mainly recognized with a constitutional aspect. Based on the results obtained, and based on the analysis carried out on the study of the demarcation of brazilian navy lands, based on the national characterization plan developed by the spu, it was verified that much remains to be done in relation to the demarcations and, the importance of the navy land remaining as assets of the union, overcoming the lack of instruments and advancing to the recognition of the constitutional expression of this institute and in this way, the research went to the creation of a "normative act" in the species "recommendation", to the technicians of the municipal government of abaetetuba, who are involved with the public service situations inherent to the marine lands.